Characterization and performance of plate-like Ba0.6Sr0.4TiO3/Poly(vinylidene fluoride – trifluoroethylene -chlorotrifluoroethylene) composites with high permittivity and low loss. (26th August 2020) - Guo, Yiting; Meng, Nan; Zhang, Yiming; Xu, Jie; Pawlikowska, Emilia; Wu, Changying; Szafran, Mikołaj; Gao, Feng
Abstract: Plate-like Ba0.6 Sr0.4 TiO3 /Poly (vinylidene fluoride - trifluoroethylene -chlorotrifluoroethylene) (P-BST)/P(VDF-TrFE-CTFE) functional composite films were prepared via a tape casting method. All samples have textured microstructure, and the orientation degree of the composites is above 50%. Though pure terpolymer has a low dielectric permittivity (20.4) and a high loss (0.52), the introduction of ceramic particles can effectively enhance its permittivity as well as decrease the loss. The composite filled with 40 vol% ceramic fillers showed a high permittivity of 88.3 as well as a low loss of 0.056 accompanying with a high dielectric tunability about 30%. Additionally, the dielectric tunable theoretical model of the composite was investigated. The functional relationship between phenomenological coefficient ratio β 1 /β 2 and the ceramic content was obtained. The final results indicate that the value of β 1 /β 2 is inversely proportional to the ceramic phase content, as opposed to the composites matrix's dielectric constant which cannot be tuned by the electric field. Graphical abstract: Image 1 Highlights: Ba0.6 Sr0.4 TiO3 /P(VDF-TrFE-CTFE) composites have a high permittivity of 88.3 and low loss of 0.056 via tape casting method. The dielectric tunability of composites reaches ∼30% when the applied field is 20 kV/mm. The dielectric tunability of P(VDF-TrFE-CTFE) has a great influence on the tunable property of composite material system. The value of β 1 /β 2 is inversely proportional to ceramic content for composites whose matrix's permittivity can be tuned.